Green and Digital Leadership: Impact on Sustainable Performance, Mediating Environmental Knowledge Sharing, Moderating Technological Innovation - Yahya, Aiyub; ., Adnan; Rozik, Teuku Adya; Nabil, Said Afif (Journal of Ecohumanism, 2024)
This study aims to explore the influence of Green Leadership and Digital Leadership on Sustainable Performance through the mediating role of Environmental Knowledge Sharing and the moderating role of Technological Innovation. Data were collected from 365 employees of District regional secretariat in North Aceh Regency, Bireuen Regency, and Lhokseumawe City, Indonesia, using a quantitative method with Structural Equation Modeling (SEM) employing Smart PLS software. The findings reveal that both Green Leadership and Digital Leadership significantly impact Environmental Knowledge Sharing. While Digital Leadership does not directly influence Sustainable Performance significantly, both Digital Leadership and Environmental Knowledge Sharing exhibit a positive and significant effect on Sustainable Performance. Environmental Knowledge Sharing significantly mediates the influence of Green Leadership and Digital Leadership on Sustainable Performance. Moreover, Technological Innovation moderates the relationship between Environmental Knowledge Sharing and Sustainable Performance, indicating a reduction in impact at higher levels of innovation. Theoretical implications of these findings extend understanding of how Digital Leadership and Green Leadership affect sustainable performance through environmental knowledge dissemination. Practical implications suggest organizations should prioritize developing digital and green leadership competencies to enhance their environmental knowledge and sustainable performance.